ANALISIS PENGARUH DAMPAK MAKROEKONOMI, KEBIJAKAN PEMERINTAH, DAN KINERJA PERUSAHAAN TERHADAP RETURN SAHAM SEKTOR INFRASTRUKTUR - Achmad Usman Maulana; David Kaluge (Contemporary Studies in Economic, Finance and Banking, 2024)
Infrastructure sector stocks experienced a stable and upward trend, even sharply at the end of quarter 2023. In line with the government budget in infrastructure development that continues to increase, supported by the increase in this sector, one of which will contribute to increasing economic growth in Indonesia, therefore the purpose of this research is to analyze the effect of macroeconomic impacts, government policies, and company performance on infrastructure sector stock returns. Inferential quantitative research with panel data regression analysis techniques is included in this research. With purposive sample method, ten companies were selected, out of 62 companies in the whole population. The type of secondary data is quarterly for the period 2016-2022. The implications of this research as material for investors to invest. Common Effect Model (CEM) is the selected model, the findings prove that partially interest rates, capital expenditures, CR, TATO, ROE, PER, DER, ROA, EPS, NPM, DPR, and DPS have no effect on stock returns. PBV has a significant positive effect on stock returns. Exchange rate, inflation, and DY variables have a significant negative effect on stock returns. Simultaneously, exchange rate, inflation, interest rate, capital expenditure, CR, TATO, ROE, PER, DER, ROA, EPS, PBV, NPM, DPR, DPS, and DY all affect stock returns.